Optimal control of nonlinear second order evolution equations. (1993) - Ahmed Ahmed, N. U. N. U.; Kerbal Kerbal, Sebti Sebti
Abstract : In this paper we study the optimal control of systems governed by second order nonlinear evolution equations. We establish the existence of optimal solutions for Lagrange problem.